Effects of hydrothermal oxidation time of Al on the catalytic performance of Ru/Al@Al2O3 for selective oxidation of CO in H2 - Kim, Jieun; Kim, Tae Wook; Kim, Han Bom; Kang, Jong Kyu; Park, Eun Duck (Fuel, 2021)
The thermal-conducting support is highly desirable for endothermic and exothermic reactions as long as highly dispersed active sites can be maintained. The core-shell Al@Al2O3 supports with different aluminum (Al) contents were prepared from Al particle by controlling the reaction time during hydrothermal surface oxidation and applied as a support to the supported Ru catalysts for preferential CO oxidation in H2 (PROX). The prepared catalysts were characterized by N2-physisorption, X-ray diffraction, CO chemisorption, scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), X-ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM), in situ diffuse reflectance infrared Fourier transform spectroscopy after CO adsorption (CO-DRIFTS), and temperature-programmed desorption of ammonia (NH3-TPD) and ethanol (ethanol-TPD). The catalytic activity was dependent on the Al content in the Al@Al2O3 support. The most active Ru/Al@γ-Al2O3 catalyst oxidized CO selectively in H2 over a wide reaction temperature. The surface property of the outermost exterior alumina layer in the Al@γ-Al2O3 support, determined with ethanol TPD, was beneficial for formation of Ru nanoparticles with weak adsorption of CO, probed with CO-DRIFTS, results in the high catalytic performance for PROX.
Keywords: Aluminium content; Aluminum@aluminum2O3; Catalytic performance; Hydrothermal oxidation; Oxidation time; Preferential CO oxidation; PROX; Ru; Thermal; ]+ catalyst; Al@Al2O3; Preferential CO oxidation; PROX; Ru; Thermal conductivity